A Novel TGF-β Risk Score Predicts the Clinical Outcomes and Tumour Microenvironment Phenotypes in Bladder Cancer - Liu, Zhi; Qi, Tiezheng; Li, Xiaowen; Yao, Yiyan; Othmane, Belaydi; Chen, Jinbo; Zu, Xiongbing; Ou, Zhenyu; Hu, Jiao (Frontiers in Immunology, 2021)
Background: The TGF-β pathway plays critical roles in numerous malignancies. Nevertheless, its potential role in prognosis prediction and regulating tumour microenvironment (TME) characteristics require further elucidation in bladder cancer (BLCA). Methods: TGF-β-related genes were comprehensively summarized from several databases. The TCGA-BLCA cohort (training cohort) was downloaded from the Cancer Genome Atlas, and the independent validation cohorts were gathered from Xiangya Hospital (Xinagya cohort) and Gene Expression Omnibus. Initially, we identified differentially expressed TGF-β genes (DEGs) between cancer and normal tissues. Subsequently, univariate Cox analysis was used to identify prognostic DEGs, which were further used to construct the TGF-β risk score by performing LASSO and multivariate Cox analyses. Then, we explored the role of the TGF-β risk score in predicting prognosis and the TME phenotypes. In addition, the role of the TGF-β risk score in guiding precision treatments for BLCA has also been assessed. Results: We successfully constructed a TGF-β risk score with an independent prognostic prediction value. We also found that a high TGF-β risk score indicated an inflamed TME phenotype, which was supported by the positive correlations between the risk score, activities of anticancer immunity cycles, and the infiltration levels of tumour-infiltrating immune cells. Meanwhile, the risk score was positively related to the expression of several immune checkpoints and the T cell inflamed score. Consistently, the risk score was positively associated with the enrichment scores of most immunotherapy-positive gene signatures. In addition, the sensitivities of six common chemotherapeutic drugs were positively associated with the risk score. Furthermore, patients with higher risk scores were more sensitive to cancer radiotherapy, and EGFR targeted therapy. In contrast, patients with low-risk scores were more sensitive to targeted therapies, including the blockade of FGFR3 and WNT-β-catenin networks. Conclusions: We first developed and validated a TGF-β risk score that could predict the clinical prognosis and TME phenotypes of BLCA. More importantly, the TGF-β risk score may aid in individual precision treatment for BLCA.